Wiley not-for-profit GAAP 2015 : interpretation and application of Generally Accepted Accounting Principles - Larkin, Richard F.; DiTommaso, Marie; Ruppel, Warren (Chichester, West Sussex, United Kingdom : John Wiley & Sons Ltd, 2015)
"Detailed, practical coverage of GAAP, tailored to not-for-profit organizations. Wiley Not-for-Profit GAAP 2015 is a thorough examination of the authoritative standards for measurement, presentation, and disclosure as applied to not-for-profit organizations. Clear and concise, this user-friendly guide explains the fundamentals of GAAP in an easily-accessible format that includes flowcharts and diagrams to help facilitate the reader's understanding of the material presented, including a financial statement disclosure checklist to confirm GAAP adherence. Designed specifically for accountants in public practice and industry, this guide covers all relevant FASB and AICPA guidelines, to provide a complete reference tool for auditors who need a comprehensive understanding of GAAP for not-for-profit organizations. ."--Provided by publisher.
Overview of Not-for-Profit Organizations. Overview of Not-for-Profit Organizations ; Cash Versus Accrual Basis Accounting -- Basic Financial Statements. Statement of Financial Position ; Statement of Activities ; Statement of Cash Flows ; Other Financial Statement Issues -- Specific Not-for-Profit Accounting Topics. Fund Accounting ; Net Assets ; Contributions, Pledges, Noncash Contributions, and Exchange Transactions ; Investments ; Affiliated Organizations ; Split-Interest Agreements ; Fundraising and Joint Costs ; Functional Reporting ; Collections -- Other Accounting-Related Not-for-Profit Topics. Accounting for Specific Types of Not-for-Profits ; Importance of Budgets to a Not-for-Profit ; Principal Federal and State Tax Reporting and Regulatory Requirements -- General Accounting Topics Applied to Not-for-Profit Organizations. Current Assets and Current Liabilities ; Inventory ; Long-Lived Assets, Depreciation, and Impairment ; Intangible Assets ; Contingencies ; Mergers and Acquisitions ; Accounting for Pensions and Postretirement Benefits ; Long-Term Liabilities ; Accounting Changes ; Accounting for Leases ; Financial Instruments ; Capitalization of Interest Costs -- Appendix: Disclosure Checklist.
Includes index.
Online resource; title from e-book title screen (Wiley platform, viewed July 20, 2015).
Keywords: Accounting -- Standards -- United States; Nonprofit organizations -- United States -- Accounting; Accounting -- Standards -- United States; Accounting; Nonprofit organizations -- United States -- Accounting; BUSINESS & ECONOMICS -- Accounting -- Financial; Accounting -- Standards; Nonprofit organizations -- Accounting; United States; Electronic books; Electronic books